P235 The natural history of COVID-19 in vaccinated Inflammatory Bowel Disease patients. (21st January 2022) - Viazis, N; Theodoropoulou, A; Zampeli, E; Karmiris, K; Tzouvala, M; Bamias, G; Koutroubakis, I; Liatsos, C; Koustenis, K; Veretanos, C; Papathanasiou, E; Zacharopoulou, E; et al.
Abstract: Background: Patients with Inflammatory Bowel Disease (IBD), especially those on immunosuppressive (IMS) treatment should be vaccinated against SARS-CoV-2 to prevent hospitalization, mechanical ventilation, and death. However, IMS may adversely affect vaccination, raising concerns as to how vulnerable these patients are to break through COVID-19 infections. Thus, we aimed to assess the proportion of IBD patients who despite complete vaccination developed COVID-19, as well as the course of the infection. Methods: This study was an initiative of the Hellenic Group for the study of IBD which involved seven IBD referral Centers. Patients attending these Centers who reported a COVID-19 infection at least 3 weeks after vaccination completion were asked to complete an on-line anonymous questionnaire which included patient demographics and IBD clinical and therapeutic data, a detailed vaccination history, and the course and outcome of COVID-19, especially the need for hospitalization, oxygen supply, and admission to ICU. In patients with grave outcome information was sought by family members Results: On estimate, 2940 patients reported full vaccination (Pfizer vaccine) in the 7 centers. Between 1 st May 2021 and 30 th October 2021, 46 (1.5%) fully vaccinated IBD patients reported COVID-19 infection [25 male, 32 CD, 14 UC, mean (SD) age 40.8 (13.7) years, mean (SD) IBD duration mean, 11.2 (10.8) years]. Five patients were receiving 5-ASAs, 2 corticosteroids, 5 azathioprine/methotrexate, 23 anti-TNFs as monotherapy and 3 in combination with azathioprine/methotrexate, and 1 with corticosteroids, 3 vedolizumab and 1 each ustekinumab, tofacitinib and rizakinzumab at the time of COVID-19 diagnosis; one patient was receiving no treatment. IBD was in remission in 37/46 patients (80.4%). Comorbidities were seen in 21 patients (thyroid disease 11; diabetes mellitus 2; hypertension 2; psoriasis 1; prior breast cancer 1; spondyoartropathy 2; dyslipidemia 1; and PSC 1 patient). The mean (SD) time between last vaccination dose and infection was 3.2 (1.4) months. Overall, 40 (86.9%) patients reported mild constitutional and respiratory symptoms, 4 (8.7%) were asymptomatic and only 2 patients (4.3%) required hospitalization which was uneventful in both. None needed high flow oxygen supply or ICU admission, and none reported symptoms of long COVID. No deaths were reported by patient relatives. IBD medications were stopped in 21 patients (45.6%) during the COVID-19 infection. Conclusion: A minority of fully vaccinated IBD vaccinated patients developed COVID-19 which was relatively mild and uneventful. These results reinforce the importance of vaccination especially in vulnerable populations.